A Comparative Study of Shade-Matching Reproducibility Using an Intraoral Scanner and a Spectrophotometer - Franciele Floriani; Carlos A. Jurado; Salahaldeen Abuhammoud; Marcos Vargas; Nicholas G. Fischer; Silvia Rojas-Rueda; Guilherme Carpena Lopes (MDPI AG, 2024)
Background: We compared the repeatability of the shade determination of resin composite restorations and acrylic teeth in light and darker shades at baseline and after an aging process through two digital tooth color-matching methods: using a Trios 3Shape intraoral scanner and using a Vita Easyshade Compact spectrophotometer. Material and Methods: Forty upper central incisor acrylic teeth in the shade A1 (n = 10) and A3 (n = 10) were randomly assigned to be restored with Filtek Bulk Fill in the shade A1 (n = 10) or A3 (n = 10). Subsequently, 20 Class V cavities were prepared in a standardized manner (mesio-distal = 3.0 mm, cervical-occlusal = 2.0 mm, depth = 1.5 mm). Cavities were restored using an universal adhesive system and resin composite in two increments and were light-cured. The shade difference between the resin composite Class V restorations in acrylic teeth of the A1 and A3 shades was evaluated at baseline and after aging. Aging was simulated using ultraviolet light for 120 h. An Easyshade device and an intraoral scanner were used under D65 illumination. Measurements were taken five times, on top of the restoration and on the acrylic teeth, in a randomized manner. Results: Data analysis was on the calculation of the arithmetic mean for the percentage of repeatability conducted by the Trios scanner and the Easyshade device. There was no statistically significant comparison between the shade measurement devices (p > 0.05). At baseline, the repeatability for both the Trios intraoral scanner and the Vita Easyshade Compact device for artificial teeth in the shades A1 and A3 was 100%. After aging, the trueness recorded by the intraoral scanner and the Easyshade device for artificial teeth in the shade A1 was 80%. For Class V restoration with shade A1, the intraoral scanner recorded 80% trueness and the Easyshade device recorded 60% trueness at baseline. For shade A3, the intraoral scanner recorded 60% trueness and the Easyshade device recorded 60% trueness. Conclusions: The intraoral scanner and Easyshade device are reliable for baseline shade selection, but their accuracy decreases after aging, particularly for darker shades.